Evaluating Kahoot and Practicum Effectiveness in Enhancing Understanding of Cost and Management Accounting: Evaluasi Efektivitas Pembelajaran Interaktif dengan Kahoot dan Praktikum dalam Meningkatkan Pemahaman Mahasiswa pada Mata Kuliah Dasar Akuntansi Biaya dan Manajemen - Retta Farah Pramesti; Rosyani Muthia; Efri Elsridayani Purba; Deasy Emalia (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Game-based learning technology such as Kahoot has been widely used in higher education to increase student engagement. However, little research has evaluated its impact on student understanding in Basic Cost and Management Accounting courses. Therefore, this study aims to measure the effectiveness of Kahoot-based learning methods and practice questions in improving student understanding. This study used a pre-test-post-test design without a control group and used a quantitative approach. The research sample comprised 32 students taking the Basic Cost and Management Accounting course. Data were collected through pre-test, post-test, and questionnaire results. Data analysis was conducted using a Paired Sample t-test to see significant differences between the pre-test and post-test and descriptive analysis to assess students' perceptions of the applied learning methods. The results of the Paired Sample t-test showed a significant increase in student understanding after participating in the learning session, with a power analysis result of 72.3% and an effect size of 1,919, indicating a strong learning impact. In addition, the questionnaire results revealed that most students felt that this method helped them understand the material better. However, some students provided input regarding adjustments in the speed of explanation, variations in learning methods, and distribution of teaching materials to improve learning effectiveness. Conclusion: Overall, this study shows that the combination of Kahoot!-based learning and problem practice effectively improves students' understanding of Basic Cost and Management Accounting. The results of this study can be the basis for developing interactive learning methods in higher education to improve the quality of accounting learning.